Analysis of failure mechanisms in fatigue test of reinforced concrete beam utilizing acoustic emission - Bunnori, N; Nor, N; Jiun, K; Kudus, S (The International Journal of Multiphysics, 2014)
The acoustic emission technique is used for monitoring the fatigue failure mechanisms in reinforced concrete beam under three point bending. The analysis was conducted by using the bathtub curve method plotted from acoustic emission data. In this study, the fatigue behavior was divided into three stages. The first stage is involved with the decreasing failure rate, known as early life failure or burn-in phase, the second stage is characterized by constant failure rate and the third stage is called the burn-out phase which is an increase of failure rate. The three parameters used in analyzing is the fatigue behavior for each stage of failure which are severity, signal strength and the cumulative signal strength. From severity analysis, the range of each stage of failure had been determined while from signal strength analysis, the initiation of distribution of crack had been detected through the fluctuation of signal strength. Cumulative signal strength parameter provides a clearer view of the initiation and distribution of crack.